Ocular and extra-ocular complications following long-term steroid consumption in children with idiopathic nephrotic syndrome - Chaudhury, Gulshan Nigar; Khandaker, Tarannum; Ferdous, Tahmina; Chowdhury, Rifat Asma; Afroz, Shireen; Hanif, Mohammed (BIRDEM Medical Journal, 2020)
Background: High dose of corticosteroids are required by patients with idiopathic nephrotic syndrome for long duration due to repeated relapse. The aims of this study were to analyze the ocular and extra-ocular complications of steroids on children with nephrotic syndrome. Methods: This cross-sectional study was conducted at Dhaka Shishu (Children) Hospital from September 2017 to September 2019. Children with nephrotic syndrome between 1-16 years of age, who received steroid for at least three months, participated in this study. Total 70 children were enrolled. Detailed history was taken from parents regarding initial episode, drug history, visual problem, headache, hypertension, weight gain, psychosis, bone pain, epigastric pain and excessive growth of body hair. Comprehensive opthalmologic assessment including visual acquity, intraocular pressure and cataract were performed. Detail of renal histopathology and treatment regimen in each patient was noted. Results: A total of 70 patients were included, 61.4% were male and 38.6% were female. Median age at the time of examination was 60 months (range 17 to 216 months). The mean duration of disease was 33.71±21.12 months. The mean cumulative steroid dose at the time of examination was 8485.91±7326.83 mg. Fourteen (20%) patients had posterior subcapsular cataract. Among 70 patients, we could do visual acuity for 25 (35.7%) patients, intraocular pressure (IOP) in mm for 51 (72.85%) patients. Among them raised IOP was found in five (9.8%) patients. In right eye mean IOP was 14.16±3.57 and for left eye 14.77±3.55 mm. Renal biopsy was performed in 15 (21.43%) cases. Among the biopsy report, it was found that mesangial proliferative glomerulonephritis (MPGN) in 8 (53.33%), focal segmental glomerulonephritis (FSGS) in 2 (13.33%) and minimal change in 5 (33.34%) cases. Among all cases, 12 (17.14%) patients developed Cushingoid facies, 3 (4.2%) patients had hypertrichosis, 3 (4.2%) patients had central obesity and 4 (5.7%) patients had buffalo hump but none had hypertension, diabetes mellitus, epigastric pain, bone pain or psychosis. Conclusion: Cataract formation was the most frequent ocular complication after large dose of oral corticosteroid therapy. The present study emphasizes the need for regular eye screening. Cushingoid facies was the most frequent among extra-ocular complications. Birdem Med J 2021; 11(1): 7-10